STRATEGI PENGEMBANGAN BISNIS TAMBAK IKAN BANDENG DI DESA MENGARE WATUAGUNG GRESIK - Nanda Aulia, Ersa (Profit: Jurnal Adminsitrasi Bisnis, 2021)
This research was conducted to analyze the factual conditions in the milkfish pond business, find out the development business strategy, and compile a business plan for milkfish pond business development. This study uses data analysis methods in the form of in-depth interviews, observation and documentation. From the results of the research the factual business conditions on the technical aspects including pond preparation, fertilizing and eradicating pests, acclimatization and spreading nener, feeding, and harvesting have been going well. In the management aspect which consists of planning, organizing, moving, and supervising according to business functions. In the marketing aspects including marketing mix, marketing channels, marketing margins and ways of payment have been distributed to consumers. In the calculation of short-term and long-term financial aspects it can be concluded that this business is profitable and feasible to run financially. The business development strategy with the SWOT analysis is located in quadrant I, which supports aggressive growth policies using the SO (Strength Opportunities) strategy. The strategy used is to maintain the quality of milkfish, conduct training with field extension workers, utilize natural resources, facilities and infrastructure to support business and optimize this business for the better by looking at financial aspects that are viable.